Erectile dysfunction in patients with diabetes mellitus: results of epidemiological monitoring - Roman Viktorovich Rozhivanov; Yury Ivanovich Suntsov; Dmitriy Gennad'evich Kurbatov (Сахарный диабет)
Aim. Screening for erectile dysfunction (ED) in patients with type 1 and 2 diabetes mellitus. Materials and methods. The study included 611 patients with type 1 (n=276) and 2 (n=335) diabetes mellitus. The control group comprised 70 patients.The methods used were a questionnaire survey, HbA1c measurement, evaluation of renal and cardiovascular function, examination of ocularfundus, lower extremities and genital organs. Differences were considered significant at p